Offensive hacking unfolded Become a pro Pentester (Packt Publishing, 2022)
Learn to perform professional penetration testing using real-world corporate methodologies and prepare industry-grade reports. About This Video Learn how to use Metasploit framework to ease the process of exploitation Go specifically deep into hacking web technologies, applications, and servers Learn how to beat the security of custom websites having specific vulnerabilities In Detail In this course, you will learn the very basics of installing VMware and what to do to create the virtual environment that contains both our hacker machine and the target labs. Learn how to do advanced information gathering and reconnaissance in both active and passive modes as well as get the required templates and guides that will explain to you how to store the data you have gathered in a professional way. After that, we will take the data that was gathered in the previous section and use it to conduct vulnerability assessments. Moving ahead, we will also discuss how to use the Metasploit framework to ease the process of exploitation without neglecting the way to exploit things manually. Next, we will see how to beat the security of custom websites having specific vulnerabilities such as SQL injection, Cross Site Scripting (XSS), unrestricted file uploads, command injection, and brute forcing. Learn post exploitation with and without Metasploit framework as well as know many manual methods to do privilege escalation on a target, to move from standard user access to a full root/admin level shell. In the last and final section of the course, we will focus on how to write a report in a professional format. By the end of the course, you will be able to perform professional penetration testing in real life. Audience This course is for anyone curious about practical hacking and for people wanting to become advanced pentesters. It can also be taken by students willing to explore security testing. Knowing the basics of Linux and networking as well as knowing the extreme basics of hacking will be an added advantage.